Risk, ambiguity and willingness to participate in crop insurance programs: Evidence from a field experiment - Williams Ali; Awudu Abdulai; Renan Goetz; Victor Owusu (Australian Journal of Agricultural and Resource Economics, 2021)
This paper analyses smallholder farmers' willingness to participate in crop insurance programs, using recent data from cocoa farmers in Ghana. Given the significance of output uncertainty and imperfect capital and insurance markets, we develop a theoretical framework to analyse how risk and ambiguity aversion, and liquidity constraints influence farmers' crop insurance participation decisions. We employ field experiments to elicit farmers' ambiguity and risk aversion, the stated preference approach to obtain information on farmers' willingness to participate in crop insurance programs, and a discrete choice model to examine the factors that influence their participation decisions. We find that risk preferences, ambiguity aversion, and liquidity constraints influence farmers' willingness to participate in crop insurance programs. The results also reveal that the probability of participating in crop insurance programs is positively influenced by wealth, trust and education of the farmers.
Keywords: 330; ambiguity aversion; crop insurance; field experiments; liquidity constraints; risk aversion